YIELD PERFORMANCE AND ECONOMIC RETURN OF MAIZE AS AFFECTED BY NUTRIENT MANAGEMENT STRATEGIES ON FERRALSOLS IN COASTAL WESTERN AFRICA - Detchinli, K. S.; Sogbedji, J. M. (European Scientific Journal, ESJ, 2015)
We assessed maize (Zea mays L.) grain yield and associated economic returns of four soil fertility management strategies in a 2-yr study (four growing seasons). The Ikenne maize cultivar was used and the fertilization treatments included: no fertilizer application (control, T1), application of farmyard manure (FYM) at the rate of 6 Mg ha-1 (T2), the agricultural services recommended maize-based fertilization consisting of 200 kg N15P15K15 plus 100 kg urea (46% N) ha-1 (T3) and application of 3 Mg of FYM plus 100 kg N15P15K15 plus 50 kg urea (46% N) ha-1 (T4). On the 2-yr period basis, four-season cumulative grain yields under T4, T3 and T2 were 40, 25 and 22% higher as compared with T1, respectively, those under T4 and T3 were 15 and 3% higher as compared with T2, respectively, while the yield under T4 was 12% higher than that under T3. For the 2-yr period, on a per hectare basis, economic profits under T4, T3 and T2 were 69 and 31% higher and 10% lower as compared with T1, respectively, profits under T4 and T3 were 87 and 46% higher as compared with T2, respectively, while profit under T4 was 28% higher than that under T3. In the current context of degraded soils in coastal western Africa, T4 reflecting a combined application of mineral fertilizer at the rate of N38P15K15 ha-1 plus organic amendment as FYM at the rate of 3 Mg ha-1 should be advised towards sustaining enhanced maize crop productivity and profitability.